2004
DOI: 10.1016/j.ipl.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Factoring stochastic relations

Abstract: When a system represented through a stochastic model is observed, the equivalence of behavior is described through the observation that equivalent inputs lead to equivalent outputs. This paper has a look at the systems that arise when the stochastic model is factored through the congruence. Congruences may refine each other, and we show that this refinement is reflected through factoring. We also show that factoring a factor does not give rise to any new constructions, since we are kept in the realm of factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Morphisms will be used for comparing interpretations; they will be based on morphisms for stochastic relations [9,13], cp. [6].…”
Section: Stochastic Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphisms will be used for comparing interpretations; they will be based on morphisms for stochastic relations [9,13], cp. [6].…”
Section: Stochastic Relationsmentioning
confidence: 99%
“…All these constructions may be undertaken in the uniform framework of a suitable category [9,13], making for a more concise formulation. We refrain from a systematic algebraic interpretation here, however, and use this notation only occasionally.…”
Section: Stochastic Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It becomes easier to investigate the bisimilarity of stochastic relations: for example, it can be shown that two stochastic relations are bisimilar provided they have isomorphic factors; the converse holds under the assumption of compactness as well, so one might speculate whether bisimilarity and having isomorphic factors are equivalent, see (Doberkat 2004b) for a more comprehensive discussion. These investigations require us to study congruences for stochastic relations (Doberkat 2004a).…”
Section: Applicationsmentioning
confidence: 99%
“…Analytic spaces have the nice property that they are closed under factorisation of smooth equivalence relations that occur quite naturally for stochastic relations. The existence of semi-pullbacks helps in investigating these congruences, see Doberkat (2004a) for some first results. Based on the result derived here, and on an Isomorphism Theorem for them, it can be shown that two stochastic relations are bisimilar provided they have isomorphic factors; the converse also holds under the assumption of compactness -see Doberkat (2004b).…”
mentioning
confidence: 99%